Immunoresolving actions of oral resolvin D1 include selective regulation of the transcription machinery in resolution‐phase mouse macrophages. Issue 7 (1st April 2014) - Recchiuti, Antonio; Codagnone, Marilina; Pierdomenico, Anna Maria; Rossi, Cosmo; Mari, Veronica Cecilia; Cianci, Eleonora; Simiele, Felice; Gatta, Valentina; Romano, Mario
ABSTRACT: Resolvin D1 (RvD1; 7 S, 8 R, 17 S ‐trihydroxy‐4Z, 9 E, 11 E, 13 Z, 15 E, 19 Z ‐docosahexaenoic acid) is an endogenous immunoresolvent that regulates acute inflammation and orchestrates resolution. Here, we investigated anti‐inflammatory and proresolving actions of RvD1 after oral administration. RvD1 rapidly accumulated in the mouse plasma after oral delivery and dose‐dependently (1–100 ng/mouse) reduced leukocyte infiltration in zymosan A‐induced acute peritonitis. Using mathematical resolution indices, RvD1 reduced Ψmax by ~50%, shortened the resolution interval by 3 h, and significantly reduced total leukocyte (by ~30–45%) and polymorphonuclear neutrophil (by ~40–55%) accumulation when administered at the peak of peritonitis. RvD1 also improved course and outcome of severe peritonitis, shifting it toward resolution. In peritoneal macrophages (MΦs) from the resolution phase of peritonitis, RvD1 down‐regulated (by 2‐ to 3‐fold) select genes that control gene transcription, namely coactivator‐associated arginine methyltransferase 1 (CARM1), and downstream genes, such as colony‐stimulating factor 3, intercellular adhesion molecule 1, and monocyte inflammatory protein 2, which promote neutrophil infiltration and reduce MΦ phagocytosis. Congruently, CARM1 knockdown in human and murine MΦs induced a proresolving phenotype, recapitulating in vivo actions of RvD1. These results establish novel properties of RvD1 and demonstrate that RvD1 modifies the transcription control machinery in MΦs, as part of its mechanisms of action during the resolution of acute inflammation.—Recchiuti, A., Codagnone, M., Pierdomenico, A. M., Rossi, C., Mari, V. C., Cianci, E., Simiele, F., Gatta, V., Romano, M. Immunoresolving actions of oral resolvin D1 include selective regulation of the transcription machinery in resolution‐phase mouse macrophages. FASEB J . 28, 3090–3102 (2014). www.fasebj.org